A Hajdú-Bihar megyei felnőttképzés történelmi, társadalmi, gazdasági háttere (Acta Scientiarum Socialium, 2012)
This study has been written with the aim of providing an overall picture of the historic, social and economic background affecting adult education in Hungary in general and in Hajdú-Bihar county in particular. Based on the literature of the field we have made an attempt to describe and analyse statistical data in order to attract attention to the phenomenon that plays a significant role in adult education and promotes the integration of disadvantaged groups. The aim was to provide a diagnosis and a starting-point for a project in which Debrecen Reformed University of Theology and the Christian University of Partium were involved. The long term aim of the project was to promote the integration of disadvantaged people in the region, while a more immediate aim was to establish a joint adult education centre which provides further training for adult education ex-perts. On the basis of these aims in the study the economic, social and demographic characteristics of the region are described. After analysing the marginal situation of the ethnic minority and the disabled, we reveal the distinctive characteristics of adult education and the opportunities of disadvantaged groups. The challenges of adult education, the problem of globality and locality and the significance of lifelong learn-ing are also discussed.